Jumping spiders of the genus Scopocira Simon, 1900 (Araneae: Salticidae: Amycoida) from Colombia, with the description of a new species - Galvis, William (Zootaxa, 2015)
The neotropical genus Scopocira was described by Simon (1900) to include the type species S. dentichelis Simon, 1900 from Venezuela, and S. tenella Simon, 1900 and S. histrio Simon, 1900 from Brazil. Subsequently, different authors, such as Mello-Leitão (1922, 1941), Chamberlin & Ivie (1936), Crane (1945), Galiano (1958, 1963, 1969, 1981, 1982),Vedel et al. (2013) and Rubio (2014), made additions, changes, transfers and new reports in the genus. Recently, Costa & Ruiz (2014) presented a taxonomic revision of Scopocira, validating six of the previously described species and describing eight new species from South America, increasing the known diversity of the genus up to 14 species. Species of Scopocira can be recognized by the presence of one apophysis on the prolateral face of the male chelicerae and embolus arising from the retrolateral side of the tegulum in the male palps (Galiano 1958; Costa & Ruiz 2014). While comparing material from Colombia to the illustrations of the revision (Costa & Ruiz 2014), it was possible to identify a new species and the undescribed female of one species described in that paper. The new species is described here, based on specimens collected in the Amazonian department of Vaupés, Colombia. Also, the female of S. crotalica Costa & Ruiz, 2014 is described and illustrated for the first time, based on material from the Amazonian state of Guainía, Colombia. Additionally, S. dentichelis Simon, 1900 and S. tenella Simon, 1900 are also newly recorded from this country.